FEATURES OF IMMUNE DISTURBANCES IN COMMUNITY-ACQUIRED PNEUMONIAS - G. A. Mavziutova (SPb RAACI, 2014)
Abstract. Clinical and immunological examination was performed in a group of 120 patients with community-acquired pneumonia. The study included determination of humoral and cellular immunity factors, T-lymphocytes, T cell subpopulations and B cells in peripheral blood, measurements of circulating immune complexes, phagocytic activities of peripheral neutrophils, studies of cytokines (IL-2, IL-4, IL-6, IL-8, TNFalpha) in the course of disease. Abnormalities of immune response were found that determined the severity of pneumonia and extent of inflammatory lung affection. Insufficiency of phagocytic protection and abnormality of immune complex elimination, reduced activity of effector T cells, with underlying increased reaction of NK cells, deficiency of humoral immunity factors, as reduced B-lymphocyte levels, as well as a trend to decrease in in IgM and IgG levels, may, in sum, determine a severe clinical course, along with lobular affection of lungs in community-acquired pneumonia. Imbalance of cytokines, with predominant proinflammatory activity and reduced regulatory functions may represent a significant reason of these immune disturbances, thus justifying a need for development of immunomodulatory therapy.